Candida glabrata species complex prevalence and antifungal susceptibility testing in a culture collection: First description of Candida nivariensis in Argentina - Morales López, Soraya Eugenia (2016)
The presence of the cryptic species belonging to the Candida glabrata complex has not been studied in Argentina. We analyzed a collection of 117 clinical isolates of C. glabrata complex belonging to a National Culture Collection of Instituto Nacional de Microbiología “Dr. Carlos G. Malbrán” from Argentina (40 isolates from blood samples, 18 from other normally sterile sites, 20 from vagina, 14 from urine, 7 from oral cavity, 3 from catheter, 1 from a stool sample and 14 isolates whose clinical origin was not recorded). The aims of this work were to determine the prevalence of the cryptic species Candida nivariensis and Candida bracarensis and to evaluate the susceptibility profile of isolates against nine antifungal drugs. Identification was carried out by using classical phenotypic tests, CHROMagar™ Candida, PCR and MALDI-TOF. The minimal inhibitory concentrations of amphotericin B, 5-fluorocytosine, fluconazole, itraconazole, voriconazole, ketoconazole, posaconazole, caspofungin and anidulafungin were determined according to the EDef 7.3 (EUCAST) reference document. Of the 117 isolates, 114 were identified as C. glabrata and three as C. nivariensis by using PCR and MALDI-TOF. There were no major differences between C. nivariensis and C. glabrata susceptibility profiles. No resistant strains were found to echinocandins. We have found that the percentage of C. nivariensis in our culture collection was 2.56. This is the first description of C. nivariensis in Argentina, and data obtained could contribute to the knowledge of the epidemiology of this cryptic species.